EXPERIMENTAL RESEARCH OF WOODEN I- BEAMS WITH WEB OF ORIENTED STRAND BOARD (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper presents constructive solutions ofcomposite beams, shown the results of experimental research and defined features of their destruction of I- beams with web of oriented strand board. Keywords:wooden beam composite section, wooden frame, oriented strand board, glued constructions.